Effects of organic acid blends on the growth performance, intestinal morphology, microbiota, and serum lipid parameters of broiler chickens - Swapnali Waghmare; Mahesh Gupta; K.B. Bahiram; J.P. Korde; Rekha Bhat; Yashwant Datar; Pushpendra Rajora; M.M. Kadam; Megha Kaore; N.V. Kurkure (Poultry Science)
Organic acids have emerged as promising alternatives to antibiotic growth promoters in poultry production. The present study was conducted to determine the effects of organic acids blends v.i.z. Acidapure liquid and Acidapure powder supplementation on the growth performance, gut health, gut microbiota, and serum lipid profile of broiler chickens. A total of 120-day-old chicks with similar live body weights were randomly divided into four groups. Each group was further divided into 3 replicates, and each further divided into three replicates of ten bird. The birds in Group 1 (T1) were fed a basal diet supplemented with plain drinking water, those in Group 2 (T2) received basal feed supplemented with Acidapure powder (1 kg/MT feed) and plain drinking water, those in Group 3 (T3) received basal feed supplemented with Acidapure liquid in the drinking water (0.2 ml/l water), and those in Group 4 (T4) received basal feed supplemented with Acidapure powder (1 kg/MT feed) and Acidapure liquid in the drinking water (0.2 ml/l water). Acidapure powder and Acidapure liquid were added to the feed and water of the broilers from 0–42 days of life. The results showed that compared with the control (T1), supplementation with Acidapure powder and liquid in broiler chickens for 42 days increased (P < 0.05) ABW and ADG and reduced FCR in the treatment groups (T2, T3 and T4). At d 21 and 42, all forms of Acidapure supplement increased the VH and CD in the jejunum and ileum and reduced the pH of the ileum. Compared with the control (T1), the combination of Acidapure powder and liquid (T4) increased the gene expression of the tight junction proteins Claudin-1 and Zona Occludense 1 (ZO-1). Compared with the control, Acidapure supplementation reduced the cecal coliform count and total viable count (TVC) and decreased the serum cholesterol and triglyceride levels. In conclusion, Acidapure, as a blend of organic acids, effectively enhances the growth performance and gut health of broilers, making it a viable and safe alternative to traditional antimicrobial growth promoters.